Self-esteem, shyness, and sociability in adolescents with specific language impairment (SLI) - Wadman, Ruth; Durkin, Kevin; Conti-Ramsden, Gina (American Speech-Language-Hearing Association, 2008)
Purpose: To determine if lower global self-esteem, shyness and low sociability are outcomes associated with SLI in adolescence. Possible concurrent predictive relationships and gender differences were also examined. Method: Fifty-four adolescents with SLI, aged between 16 and 17 years, were compared with a group of 54 adolescents with typical language abilities on the Rosenberg Self-esteem Scale and the Cheek and Buss shyness and sociability scales. Results: The SLI group had significantly lower global self-esteem scores than the group with typical language abilities. The adolescents with SLI were more shy than their peers, but the groups did not differ in their sociability ratings. Regression analysis found language ability was not concurrently predictive of self-esteem, but shyness was. Mediation analysis suggested shyness could be a partial but significant mediator in the relationship between language ability and global self-esteem. Conclusions: Older adolescents with SLI are at risk of lower global self-esteem and experience shyness although they want to interact socially. The relationship between language ability and self-esteem at this point in adolescence is complex, with shyness potentially playing an important mediating role.